Prognostic biomarkers in renal cell carcinoma: is there a relationship with obesity? - Rajandram, Retnagowri (Transl Androl Urol, 2019)
Obesity is a recognized risk factor for renal cell carcinoma (RCC) the commonest form of kidney cancer. Both obesity and RCC are serious diseases with increasing incidence yearly. This review examined certain obesity associated measurements and adipokines as detection/prognostic indicators for RCC. The obesity related measurements such as body mass index (BMI), waist circumstance (WC), waist-hip ratio (WHR) in predicting RCC are valid when used in conjunction with other risk factors such as age and sex or with histological findings. The adipokine adiponectin holds promising outcomes as a predictive marker in assessing the risk of developing RCC. In addition, tissue leptin/leptin receptor may be a distinguishing marker for RCC subtypes. However, circulating leptin may not be a suitable detection or prognostic biomarker for RCC. The other less investigated adipokines; omentin, visfatin, apelin and resistin are also expressed in RCC but their prognostic capabilities are still inconclusive. BMI, WC and adipokines may be useful additions in a nomogram which includes TNM staging and pathological grading system to detect, confirm and follow-up RCC cases.